The atmospheric nitrogen budget over the South African Highveld - Ferguson, Kirsten Sheena (My University, 2010)
Molecular nitrogen is a highly abundant element in the atmosphere; it is stable and not very reactive. Anthropogenic activities have caused greater concentrations of nitrogen-containing compounds that are highly reactive and ultimately toxic. Reactive nitrogen concentrations have become a growing concern on the South African Highveld, with satellite images indicating very high nitrogen dioxide concentrations in the region. This study investigates the nitrogen budget on the Highveld through the analysis of the nitrogen species emitted into the atmosphere on a temporal scale as well as the atmospheric conversion, transport and removal of these species. Data was collected at Elandsfontein monitoring site, which is centrally located on the industrialised Highveld. The formation and interaction of nitric oxide (NO), nitrogen dioxide (NO2), and nitrate (NO3) are a major focus in the study. NOx concentrations are higher in winter (6.5 to 8.5 μg.m-3) as a result of stable atmospheric conditions. NO3 concentrations also peak during winter (3.5 to 5.5 μg.m-3), with a distinct biomass burning peak during July and August. Diurnally, NOx concentrations indicate a tall-stack industrial source, with concentrations peaking at midday. NO3 concentrations are higher at night and lower during the day, as during the day the NO3 radical is rapidly photolysed and nitrates cannot be produced. Case studies indicate that the conversion rate of NO to NO2 is highly variable as a result of varying atmospheric factors. These rates range from 11% to 59% per hour. Rates of dry deposition of NO, NO2 and NO3 are generally higher during winter as a result of higher concentrations and increased atmospheric stability, which prevents transport out of the region. Nitrogen is predominantly deposited as NO2 throughout the year, except during spring when NO3 deposition dominates. The total amount of nitrogen deposited to the Mpumalanga Highveld region is in the range of 6.7 to 13.1 kg ha-1 yr-1, which is well below the stipulated critical load value. Such deposition therefore does not pose significant threats to the natural environment on the Highveld. Between 4% and 14% of the total emitted nitrogen on the Highveld is deposited to the surface via wet and dry deposition. The remainder stays in the atmosphere and is advected out of the region.
Keywords: Nitrogen oxides; nitrate; diurnal variations; seasonal variations; atmospheric conversion; deposition